Faktor-faktor yang mempengaruhi Audit Delay pada Perusahaan Manufaktur Sub Sektor Pulp and Paper yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Zahra, Rianti; Setiawan, Ade Budi; Didi, Didi (Universitas Pahlawan Tuanku Tambusai, 2024)
The presentation of financial reports must be delivered quickly, completely and accurately so that they can be useful and have value for stakeholders. The relevance and accuracy of financial reports will become increasingly doubtful if the financial reports are delayed for longer, the length of days of delay in publication of financial reports is what is usually called audit delay. This research aims to examine the influence of company size, profitability, solvability and audit opinion on audit delay. The object of this research is the pulp and paper sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data used is secondary data from the company's annual report. The sampling technique was purposive sampling which produced a sample of 40 samples from 8 companies over a period of 5 years. The data analysis method of this research is panel data analysis using Eviews12 software. The research results show that company size and profitability have a significant negative effect on audit delay. Meanwhile, solvability and audit opinion have no effect on audit delay.